Is the sugar intestinal permeability test a reliable investigation for coeliac disease screening?. (February 1997) - Catassi, C; Fabiani, E; Rätsch, I M; Bonucci, A; Dotti, M; Coppa, G V; Giorgi, P L
Abstract : BACKGROUND: The lactulose/mannitol (L/M) intestinal permeability test is a simple, non-invasive screening test for coeliac disease. The reliability of the L/M test has so far only been tested in selected groups of patients with coeliac disease. AIM: To evaluate the reliability of the L/M test in a group of patients with coeliac disease who had been diagnosed during mass serological screening of the general population. PATIENTS AND METHODS: Twenty nine patients with coeliac disease detected by screening and 54 age matched coeliac disease free controls aged 11-15 years underwent an L/M test with 5 g lactulose and 2 g mannitol in isotonic aqueous solution. Urinary sugars were measured by high performance liquid chromatography. RESULTS: The median % urinary recovery of lactulose (lactulose UR) was significantly higher in patients with coeliac disease than in controls (0.63 v 0.18, p < 0.001). The mean mannitol % UR was lower in patients with coeliac disease than in controls (17.6 v 18.5) but the difference was not significant. The median urinary L%/M% ratio was significantly higher in patients with coeliac disease than in controls (0.038 v 0.014, p < 0.001). However, 16 of the 29 patients with coeliac disease showed an L%/M% ratio within normal limits (< 0.044). CONCLUSIONS: The L/M intestinal permeability test is not a valuable tool for screening of coeliac disease in the general population. The pattern of the urinary probe recovery suggests that many patients with coeliac disease could remain symptomless because the extent of their intestinal mucosal damage is small ("short" coeliac disease).